FORMATION AND ENHANCEMENT OF HOUSEHOLD INCOMES IN THE REGIONAL ECONOMY - Azizbek Madiev (American Journals, 2025)
This study examines the relationship between population incomes and regional development in Uzbekistan, highlighting the socio-economic disparities that have emerged across different regions. Drawing on statistical data from 2010 to 2024, the research analyzes trends in interregional income inequality, as well as the dynamics of real and nominal incomes over time. Special attention is given to the mechanisms of state regulation and their effectiveness in reducing economic disparities and promoting balanced regional growth. The findings contribute to a deeper understanding of how income formation processes influence regional economic development and provide insights into policy measures aimed at enhancing household welfare and income equality.
Keywords: Population incomes, regional development, economic inequality, income regulation, real incomes